Comparative Study of BaY0.1Zr0.9O3-δ Protective Layers Deposited to BaY0.1Ce0.9O3-δ Membrane Using Ultrasonic Spray Pyrolysis and Magnetron Sputtering Methods. Issue 5 (1st January 2016) - Maide, Martin; Korjus, Ove; Vestli, Mihkel; Romann, Tavo; Aruväli, Jaan; Kirsimäe, Kalle; Nurk, Gunnar
Abstract : To combine chemical stability of BaY0.1 Zr0.9 O3-δ (BZY) and good proton conductive properties of BaY0.1 Ce0.9 O3-δ (BCY) bilayer membranes were prepared. Supportive BCY membranes were prepared applying dry pressing of nanopowder, which was synthesized with ultrasonic spray pyrolysis method. Thin protective BZY coatings were prepared using ultrasonic spray pyrolysis and magnetron sputtering methods. Ultarsonic spray pyrolyzed BZY layers were 0.5–1.1 μm thick, phase pure and with some closed porosity. Protective BZY layers synthesized with reactive magnetron sputtering method were approximately 0.7 μm thick, highly dense and with good phase purity. Activation energy for BCY membrane was 0.35 eV. BZY protective layer sintered at relatively low temperatures (600 to 1150°C) had minor influence on total activation energy. Sintering at 1350°C led to a decrease of activation energy of proton transport process at grain boundary region, an increase of activation energy of proton transport in bulk and a slight increase of total activation energy. Sintering at 1350°C and higher temperatures led to interdiffusion of Zr and Ce cations between BZY and BCY phases and changes in chemical as well as electrochemical properties. Prepared membranes with BZY layer were exposed to CO2 at 700°C and were observed to be chemically stable if sintering of BZY were carried out at 1150°C and lower temperatures.